Kann Case Management den Umzug von Menschen mit Demenz in eine Pflegeeinrichtung verzögern? – Ein systematisches Review randomisiert kontrollierter Studien - Klaas-Ickler, Dorothee; Kolominsky-Rabas, Peter; Dietzel, Nikolas (Gesundheitswesen, 2023)
Background Dementia is one of the main reasons for care dependency in old age. Demographic changes will lead to decreased formal and informal care potential in Germany. The promotion of structured home care arrangements therefore becomes increasingly significant. The concept of case management (CM) aims at the efficient coordination of health care services based on the needs and resources of patients with chronic health issues and their caregivers. The objective of this review was to evaluate current studies on the effectiveness of outpatient CM approaches on delaying long-term care placement or reducing the risk of long-term care placement in people with dementia. Methods A systematic literature review of randomized controlled trials (RCTs) was conducted. Relevant electronic databases (Pubmed, CINAHL, PsycINFO, Scopus, CENTRAL, Gerolit, ALOIS) were systematically searched. Reporting and study quality was assessed using the CONSORT checklist and Jadad scale. Results The search strategies identified 6 RCTs relating to 5 different health care systems (Germany, USA, Netherlands, France, China). Three of the RCTs showed significant delays of long-term care placements and/or significantly reduced rates of long-term care placement in favor of the intervention groups. Conclusions The outcomes suggest that CM approaches have the potential of promoting the length of time that people with dementia remain in their own domestic environments. Further establishment and evaluation of CM approaches should therefore be strongly encouraged on the part of healthcare decisionmakers. When planning and evaluating CM approaches, specific barriers, and resources for the sustainable implementation of CM in existing care chains should be assessed and taken into account.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Dementia; Case management; Home care; Institutionalization; Predictors